Rotavirus vaccination and intussusception: a paradigm shift? - Volker Vetter; Priya Pereira; Bernd Benninghoff (Taylor & Francis Group, 2021)
Rotavirus (RV) is one of the leading causes of severe childhood gastroenteritis in children <5 years of age. Several countries have successfully implemented vaccination against RV disease; however, hesitancy to include RV vaccination in the national immunization program exists and relates, among other reasons, to the results of international post-licensure studies of RV vaccines that established an increased risk of intussusception (IS) in infants following immunization. IS is one of the major causes of bowel obstruction in infants between 4 and 10 months of age. Some studies have investigated the etiology of IS, including the role of natural RV infection and available evidence suggests that RV disease may be an independent risk factor for IS. In this regard, the benefit-risk profile of RV vaccination, which is recognized as positive, could potentially turn out to be even more favorable in preventing IS cases triggered by RV disease. However, further research is prompted to quantify the IS risk attributable to RV disease.